ANALISIS TERHADAP INPRES NO.7 TAHUN 2015 JO INPRES NO.10 TAHUN 2016 TENTANG AKSI PENCEGAHAN DAN PEMBERANTASAN KORUPSI KAITANNYA DENGAN PERANAN KEJAKSAAN SEBAGAI PENYIDIK - Henry Sucipto Sanjaya Sirait; Alvi Syahrin; Muhammad Hamdan; Edi Yunara (Universitas Sumatera Utara, 2018)
ABSTRACT President R.I Joko Widodo issued Presidential Instruction No. 7 of 2015 and Presidential Instruction No. 10 of 2016. Presidential Instruction No. 7 of 2015 has 8 points to be implemented. The problem of this research: How to regulate the role of the Prosecutor as an investigator in the action and prevention of criminal acts of corruption. What is the role of the Prosecutor as an investigator with the issuance of Presidential Instruction No.7 Year 2015 Jo Presidential Instruction No. 10 of 2016. What are the factors inhibiting the Prosecutor's Office as investigators of corruption prevention and eradication by issuing the Inpres. The conclusions of this research are:1.Settings role of the Prosecutor Office as investigator in action and prevention of corruption crime 2.Prosecutor's Appeal as investigator relation with the issuance of Presidential Instruction No.7 Year 2015 Jo Inpres No.10 Year 2016.3.Factor inhibiting the Prosecutor as investigator in prevention and the eradication of corruption by the issuance of the Inpres. Suggestion of this research:1. The Prosecutor through TP4D team to be involved in escort, both in budget planning, auction, implementation until the completion of procurement activities of government goods and services.2. The Prosecutor should play an active role in the enforcement of legal supermarkets and the eradication of corruption without intervention both externally and internally. 3. The Prosecutor should get additional budget by issuing the Inpres and increasing human resources in conducting investigation and prosecution of corruption crime. Keywords : Inpres, Prevention, Eradication, Corruption, Role, The Prosecutor, The Investors